Shakespeare's women and the fin de siècle - Duncan, S (2014)
Scholarship on Victorian productions of Shakespeare typically isolates Shakespeare from the rest of the repertory. My thesis illuminates how late-Victorian performances of Shakespeare and contemporary Victorian drama conditioned each other. I re-interrogate iconoclastic performances of Shakespeare’s heroines to reveal actresses’ performance networks, showing how actresses’ movements between fin-de-siècle roles created consonances between ostensibly antithetical areas of the repertoire. The performances and receptions of British actresses with high cultural capital reveal Shakespeare’s interventions into fin-de-siècle debates on gender and sexuality. Highlighting female performance genealogies, I offer the first narrative of women’s acting traditions in Shakespeare. I explore actresses’ commercial strategising, celebrity personae, theatrical innovations and contributions to Shakespearean hermeneutics. The thesis draws on significant unpublished archival material, including from private collections. Chapter One examines how the ostensibly puritanical Madge Kendal and Royal mistress Lillie Langtry used the role of Rosalind (As You Like It) within a portfolio of self-promotional strategies, inscribing their professional legitimacy and dramatising different sexual identities. Chapter Two explores how Terry’s Lady Macbeth (1888–9), interpreted as a loving wife, challenged theatrical semiotics, contemporary ideals of marriage, and perceptions of ‘good’ and ‘bad’ women. Chapter Three, on Mrs Patrick Campbell, demonstrates the success of her movements between the ‘sex-problem play’ and Shakespeare, revealing how her Shakespeare reception reflected fin-de-siècle concerns as the unwell body and mind, the figure of Salome, and the child – as both a sexual object and potentially suicidal. Chapter Four, on Terry’s Imogen (Cymbeline) discusses Shakespearean actresses’ contribution to ideas of national character and queenship, as Queen Victoria’s reign neared its end, including specific milestones such as the 1897 Diamond Jubilee. Chapter Five examines Shakespeare’s intersections with the ‘New Woman’, commodity culture and politics, as suffragists co-opted Shakespeare as a ‘suffrage’ playwright, with The Winter’s Tale’s Paulina as their icon.